(untitled) (Research in Agriculture Livestock and Fisheries, 2025)
Farm animals in Bangladesh play a crucial role in providing nutrition and are a vital component of the rural economy. This study aimed to evaluate the frequency of prevalent infectious and non-infectious diseases among farm animals in the Natore district of Bangladesh. Six Upazila Veterinary Hospitals in the Natore district of Bangladesh participated in the research from January 2023 to December 2023. We identified 76,040 clinical cases by considering the owner’s statement, conducting a general examination, observing clinical indicators, and performing laboratory diagnostics. The incidence of endoparasitic infection was the highest (47.73%), while bacterial disease infection was less frequent (1.94%). Among farm animals (cattle, buffalo, goats, sheep, and pigs) goats had the highest prevalence (54.55%) while buffaloes (3.592%) and pigs (0.068%) had the lowest prevalence. The prevalence of both infectious and non-infectious diseases was highest during the rainy season (44.37%), followed by the winter (30.48%) and summer season (25.14%). Although pig farming is uncommon in Bangladesh, we have observed the raising of pigs in the Natore district. Regrettably, parasitic infestation, specifically lice and roundworms, affects a significant number of these piglets. The frequency of lice and roundworm infestation in pigs is 0.02%. These findings suggest a significant prevalence of both infectious and non-infectious disorders. Our research reveals significant insights for prioritizing research on specific diseases and implementing efficient control strategies against them. Therefore, it is imperative for veterinarians and development partners to act to prevent and mitigate the impact of both infectious and non-infectious diseases in farm animals in Bangladesh. Res. Agric. Livest. Fish. Vol. 11, No. 3, December 2024: 327-341